2022
DOI: 10.1007/s00167-022-06872-0
|View full text |Cite
|
Sign up to set email alerts
|

The importance of joint line obliquity: a radiological analysis of restricted boundaries in normal knee phenotypes to inform surgical decision making in kinematically aligned total knee arthroplasty

Abstract: PurposeRestricted kinematic alignment (rKA) in total knee arthroplasty (TKA) aims to restore native soft tissue laxities while limiting alignment extremes that risk prosthetic failure. However, there is no consensus where restricted boundaries (RB) should be set. This study aims to determine the proportion of limbs in which constitutional alignment and joint line obliquity (JLO) would be restored with various RB scenarios, to inform decision making in rKA TKA. MethodsThe mechanical hip–knee–ankle (mHKA) angle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Femoral component rotation was not measured. Several studies [19][20][21][22] have shown that KA allows for a better restoration of the JLOA compared to MA which corroborates the findings of the present report. Furthermore, Kim et al [23] found that postoperative ankle joint line orientation after KA primary TKA was horizontal to the floor and closer to that of native ankle joints than those after MA primary TKA.…”
Section: Discussionsupporting
confidence: 93%
“…Femoral component rotation was not measured. Several studies [19][20][21][22] have shown that KA allows for a better restoration of the JLOA compared to MA which corroborates the findings of the present report. Furthermore, Kim et al [23] found that postoperative ankle joint line orientation after KA primary TKA was horizontal to the floor and closer to that of native ankle joints than those after MA primary TKA.…”
Section: Discussionsupporting
confidence: 93%
“…These latter boundaries have been validated to capture the alignments of 85.4% of normal subjects, versus 67.8% of those within the initially recommended ± 3° HKA angle. 67…”
Section: Individualized Alignment Approaches In Tkamentioning
confidence: 99%
“…Adjusted MA is the least likely of the individualized strategies to restore native JLO and soft-tissue balance as they capture only 36.2% of normal subject’s constitutional alignments. 67…”
Section: Individualized Alignment Approaches In Tkamentioning
confidence: 99%
“…Recent studies reported favourable clinical outcomes following TKA using patient‐specific alignment techniques [2, 14, 29, 30], and some surgeons are therefore more comfortable in deviating from limits imposed by mechanical alignment [17]. Yet, there is no consensus on the ‘safe zone’ beyond which long‐term survival could be compromised [3, 23, 25].…”
Section: Introductionmentioning
confidence: 99%